Bioaccessibility of Biofortified Sweet Potato Carotenoids in Baby Food: Impact of Manufacturing Process - Dhuique-Mayer, Claudie; Servent, Adrien; Messan, Charlotte; Achir, Nawel; Dornier, Manuel; Mendoza, Yery (Frontiers in Nutrition, 2018)
Orange-fleshed sweet potato (OFSP), a biofortified crop rich in β-carotene, can be used as a component of baby food recipes in order to tackle vitamin A deficiency in children less than 6 years old. In this work, the impact of formulation (addition of pumpkin, oil and egg yolk) and industrial heat processing (pasteurization, sterilization) on carotenoid content and bioaccessibility was evaluated in an OFSP-based baby puree. A commercial OFSP baby food product from Brazil and a homemade OFSP puree were used as references. The losses of all-trans-β-carotene ranged from 16%-21% (pasteurization, homemade) to 32% (sterilization). Because of higher particle sizes and despite a higher content in carotenoids, the homemade puree had a lower bioaccessibility (i.e. micellar transfer using in vitro digestion: 0.50%) compared with the sterilized and commercial purees (5.3-6.2%). Taking into account bioaccessibility and applying a 50 % conversion to retinol, a 115g baby portion of the sterilized OFSP-puree formulated with 2% oil provided 31.4 % of the daily vitamin A requirement (RDA) for children under 6 years. In comparison, 115g of homemade OFSP-puree provided only 3.5% of the RDA. Addition of pumpkin to OFSP did not improve the percentage of RDA. Interestingly, the incorporation of an emulsifier (egg yolk powder) before cooking could improve the percentage of provision by a factor of 2.7. These results showed that reaching a balance between formulation and processing is determinant to maximize carotenoid bioaccessibility of carotenoids from OFSP-based baby food.